Feasibility Analysis of Self-Owened Cayale Cayle Farming During The Rainy Season - Sari, Sarita Indah Sari; Lada, Tri Hadi Sumitra Lada; Lili, Lili; Babaro, Elza Aprilista Dara Babaro (JURNAL AGRIBISAINS, 2024)
Cayenne pepper is a type of horticulture that is very popular with the public. Demand for cayenne peppers in each region continues to increase, especially in Ngabang District, by 1.30% - 1.58% during 2022. This research aims to: (1) analyze the costs and income of cayenne pepper farming during the rainy season (2) analyze feasibility of farming cayenne pepper during the rainy season (3) analyzing pests and diseases. The data collection method used a questionnaire, with the number of respondents being 12 independent farmers. The collected data was then analyzed quantitatively descriptively. The results of the research show that: (1) The production costs of cayenne pepper farming during the rainy season in Jelau Belangiran Hamlet, Ngabang District are IDR 16,814,500 per hectare/planting season and the income is IDR 18,185,000 per hectare/planting season; (2) The R/C ratio and B/C ratio values of cayenne pepper farming during the rainy season in Jelau Belangiran Hamlet, Ngabang District are 2.08 and 1.08 so that cayenne pepper farming during the rainy season in Jelau Belangiran Hamlet, Ngabang District is feasible. to strive for; (3) pests and diseases faced by farmers when farming cayenne pepper during the rainy season, namely stem rot and fruit rot.